Dental esthetic screening index (DESI) scores among patients attending Qassim University dental clinics - Norah M Almufadhi; Ola.M. Sakr; Lina Aloufi (Elsevier, 2024)
Aim: This study aimed to evaluate dental esthetic screening index (DESI) Intraoral component scores among patients attending Qassim University dental clinics and the factors affecting these scores. Materials and methods: This was a retrospective study that included 150 participants aged 18 years or older with full upper and lower anterior dentitions. Standardized intraoral frontal photographs of the patients' upper and lower dentitions were acquired from their dental records, and the mean rank DESI intraoral scores were evaluated and compared across the demographic and dental characteristics of the study patients.The mean age of the patients sampled was 33.56; 57 % were female and 43 % were male. The mean DESI Intraoral score was 15.33. DESI scores were significantly higher in patients older than 35 years compared with subjects 35 years old or younger (p = 0.015). DESI scores were increased in patients who had anterior restorations compared with those who did not (p = 0.016). Conclusions: This was the first study of its kind to use the DESI in a large clinical setting. According to the DESI, most patients attending Qassim University dental clinics had good dentofacial aesthetics. Age and the presence of anterior restorations negatively impacted patients' dentofacial aesthetics. Sex, the nature of the chief complaint, a history of orthodontic treatments, and teeth bleaching did not affect the DESI scores.